2019
DOI: 10.1007/s00403-019-01993-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered serum level of metabolic and endothelial factors in patients with systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a chronic connective tissue disease characterized by progressive fibrosis, vascular impairment and immune abnormalities. In recent years, adipokines (mediators synthetized by adipose tissue) have been indicated as a possible missing link in the pathogenesis of SSc. The aim of this study was to investigate the serum concentration of metabolic adipose tissue factors: adiponectin, resistin, leptin and endothelial proteins: endothelin-1, fractalkine and galectin-3 in patients with syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Regarding Gal-3, we found significantly higher levels of this lectin in patients with lcSSc as compared with those transiting the diffuse variant, in line with previous findings that showed serum Gal-3 levels relatively decreased in patients with dcSSc compared with lcSSc (Taniguchi et al, 2012). Strikingly, the opposite outcome was recently reported (Stochmal et al, 2020), whereas no significant differences were reported in a smaller cohort (Koca et al, 2014). As discussed below, disparity in the treatment schemes frequently used in the different cohorts analyzed may explain these discrepancies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding Gal-3, we found significantly higher levels of this lectin in patients with lcSSc as compared with those transiting the diffuse variant, in line with previous findings that showed serum Gal-3 levels relatively decreased in patients with dcSSc compared with lcSSc (Taniguchi et al, 2012). Strikingly, the opposite outcome was recently reported (Stochmal et al, 2020), whereas no significant differences were reported in a smaller cohort (Koca et al, 2014). As discussed below, disparity in the treatment schemes frequently used in the different cohorts analyzed may explain these discrepancies.…”
Section: Discussionsupporting
confidence: 90%
“…In this line, previous studies evaluated possible differences in Gal-1 (Yanaba et al, 2016) and Gal-3 (Taniguchi et al, 2012;Koca et al, 2014;Gruszewska et al, 2020) serum levels between SSc patients and controls, and reported different paradoxical results. In addition, possible associations between Gal-3 serum levels and SSc variants (Taniguchi et al, 2012;Stochmal et al, 2020), or between this lectin and specific clinical manifestations and laboratory markers of the disease has also been documented (Taniguchi et al, 2012;Koca et al, 2014;Yanaba et al, 2016;Faludi et al, 2017;Hromádka et al, 2017;Gruszewska et al, 2020;Stochmal et al, 2020), although with highly dissimilar results. Thus, further studies are required to reconcile these paradoxical different findings and to define a possible association between galectins and SSc progression.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Pehlivan et al showed that circulating leptin levels were significantly increased by approximately 5-fold in patients with systemic sclerosis compared with those in healthy controls (75). More recently, another study which enrolled 100 patients with confirmed systemic sclerosis diagnosis and 20 healthy individuals revealed that the patients presented significantly elevated serum levels of leptin (76). The discordant results summarized above might be attributed to diverse age, sex, and race of the enrolled participants.…”
Section: Relationship Between Leptin and Systemic Sclerosismentioning
confidence: 99%
“…Circulating adiponectin levels are lower in SSc patients compared to HC (SMD = −0.638), as confirmed by a meta-analysis published in 2017 (11 studies, SSc n = 511, HC n = 341) [ 88 ] and a later published study (SSc n = 100, HC n = 20) [ 89 ]. The same meta-analysis showed, although not significantly, associations of low adiponectin levels in Caucasian and Asian ethnic groups [ 88 ].…”
Section: Adiponectin In Systemic Autoimmune Rheumatic Diseasesmentioning
confidence: 72%